The China record : an assessment of the People's Republic - Wang, Fei-Ling (Albany : State University of New York Press, 2023)
"Detailed assessment of the People's Republic of China as an alternative mode of political system and as a distinctive model of socioeconomic development"--
Political governance : people's dictatorship and the party-state -- Economic record : socialism with Chinese characteristics -- Social life : bitterness, happiness, and resistance -- Spirit and ecology : culture, ethics, and the environment -- Epilogue : from the record.
Includes bibliographical references and index.
Fei-Ling Wang is Professor of International Affairs at the Georgia Institute of Technology.
Print version record.
JSTOR
Keywords: China -- Politics and government -- 1949-; China -- Economic conditions -- 1949-; China -- Civilization -- 1949-; Chine -- Politique et gouvernement -- 1949-; Chine -- Conditions économiques -- 1949-; Chine -- Civilisation -- 1949-; POLITICAL SCIENCE / Political Ideologies / Communism, Post-Communism & Socialism; Civilization; Economic history; Politics and government; China; Since 1949